If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -21 + 6x = 33 + 9x Solving -21 + 6x = 33 + 9x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-9x' to each side of the equation. -21 + 6x + -9x = 33 + 9x + -9x Combine like terms: 6x + -9x = -3x -21 + -3x = 33 + 9x + -9x Combine like terms: 9x + -9x = 0 -21 + -3x = 33 + 0 -21 + -3x = 33 Add '21' to each side of the equation. -21 + 21 + -3x = 33 + 21 Combine like terms: -21 + 21 = 0 0 + -3x = 33 + 21 -3x = 33 + 21 Combine like terms: 33 + 21 = 54 -3x = 54 Divide each side by '-3'. x = -18 Simplifying x = -18
| 12-3x/x^2-8x+16 | | 5(g-2)+g=6g-24 | | x=log(3)15 | | x^4+11x^2-44=0 | | x^2+11x^2-44=0 | | 14j-53=73+32j | | 2n/n^2-3n | | -14p+51=57p+23 | | t-1/t^2+t | | 75+21k=19+29k | | -80=b-91 | | x(7-x)+2whenx=-4 | | 20=t-70 | | 4(x+8)-7whenx=8 | | lg(x+3)+lg(1-x)=lg(4x+8) | | v-4.7=23.8 | | 59+19f=8f+5 | | k-16=7 | | 15=c-40 | | 2+n=95 | | -54=c-38 | | a-33=66 | | 19r+39=9+4r | | -16-7x=208-42x | | 8000(d)=-5d^2+450d-1000 | | 7x-7=(-x)+1 | | 45b-83=25-9b | | 9a^2+a-30=0 | | 33x^2+x+8=12 | | x^2+6x+3=-2 | | 2=48 | | 2=48r |